2022
DOI: 10.1126/science.abj8432
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial gasdermins reveal an ancient mechanism of cell death

Abstract: Ancient origin of cell death Gasdermins are cell death proteins in mammals that form membrane pores in response to pathogen infection. Johnson et al . report that diverse bacteria encode structural and functional homologs of mammalian gasdermins. Like their mammalian counterparts, bacterial gasdermins are activated by caspase-like proteases, oligomerize into large membrane pores, and defend against pathogen—in this case, bacteriophage—infection. Proteolytic activa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
115
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 49 publications
(34 reference statements)
1
115
1
Order By: Relevance
“…This suggests that humans, like all eukaryotic life forms, evolved from a blend of 2 or more microbes. Moreover, about 65% of human genes appear to have originated in bacteria, archaea, and eukaryotic microbes ( 10 ), including, for example, the genes enabling synthesis of neurotransmitters ( 11 ) and the proteins that mediate pyroptosis ( 12 ).…”
Section: Evolution Of Relationship To Microbesmentioning
confidence: 99%
“…This suggests that humans, like all eukaryotic life forms, evolved from a blend of 2 or more microbes. Moreover, about 65% of human genes appear to have originated in bacteria, archaea, and eukaryotic microbes ( 10 ), including, for example, the genes enabling synthesis of neurotransmitters ( 11 ) and the proteins that mediate pyroptosis ( 12 ).…”
Section: Evolution Of Relationship To Microbesmentioning
confidence: 99%
“…In contrast to animals’ gasdermins, the uncharacterized proteins with predicted homology to gasdermin domains were identified after bioinformatical analyses of bacterial anti-phage defense islands. The majority are encoded adjacent to one or more genes with a predicted protease domain through examining the genomic neighborhood of bacterial gasdermin-likes ( Johnson et al, 2022 ). Some of the GSDM-associated proteases are fused to repeat domains including leucine-rich repeats, tetratricopeptide repeats, WD40 repeats, or NACHT domains frequently involved in prokaryotic samples.…”
Section: Introductionmentioning
confidence: 99%
“…While breaking of viral RNAs is inadequate to escape infections, bacteria would switch on suicide as a consequence of activation of caspase-likes by sensing viral RNAs. Another recent report claimed that the activated Runella gasdermin-likes after removal of the short C-terminal region (about 20 AAs) by the associated caspase-like protease (or a certain orthocaspase) has the capability to form mesh-like membrane pores (average 28 nm in inner diameter) and displays bactericidal activity via non-selective leakage ( Johnson et al, 2022 ) ( Figure 2B ), although how caspase-like protease becomes active was not documented. Collectively, it uncovered that the conserved gasdermin-like pore is an ancient conduit for the cellular content efflux in prokaryotes and eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of bacterial gasdermin (bGSDM) has been biochemically characterized and published in Science by Johnson et al, which bridges the gap in functional understanding of GSDM between prokaryotes and eukaryotes, and also suggests the evolutionary conservation of GSDM-mediated pyroptosis, leading to cell death. 1 In addition, the identified bGSDM adds unprecedented insights into understanding of the bacterial immunity.…”
mentioning
confidence: 99%
“…On the structural basis of bGSDM from Bradyrhizobium tropiciagri and Vitiosangium sp ., the overall architecture, particularly the NTD, exhibited strong homology consists of twisted central antiparallel β sheet, linking helices and strands. 1 Although the structural study of bGSDM revealed the absence of large alpha-helical CTD that is required to maintain the autoinhibition of mammalian gasdermins, the bGSDM recruited a molecule with the same configuration to achieve the inactivation of gasdermins. 1 The atomic model of bGSDM deciphered that the protrusion from cysteine C3 side-chain in bGSDM from Bradyrhizobium occupied a hydrophobic tunnel, which can be capped by a residue, F25 at the C-terminal domain and this feature was verified as palmitoylation.…”
mentioning
confidence: 99%